2007
DOI: 10.1111/j.1365-3016.2007.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Escherichia coli in acute diarrhoea in tribal preschool children of central India

Abstract: Five hundred and eighty preschool children belonging to tribal areas of Madhya Pradesh were followed up daily for the presence of diarrhoea for a period of 1 year. In all, 1236 episodes of diarrhoea were recorded with an average of 2.13 episodes per child per year. Stool samples were collected during 780 episodes. They were cultured to isolate Escherichia coli as well as non-E. coli enteropathogens. Ten different genes were detected to identify all diarrhoeagenic E. coli using multiplex polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
5
0
2
Order By: Relevance
“…AstA-positive EAEC were not significantly associated with diarrhoea in this study (26.1% in cases, 25.5% in controls). These results, in accordance with those reported from Nigeria (Okeke et al, 2000b), contrasted with those obtained during a similar investigation in Brazil (Zamboni et al, 2004) and in India (Anvikar et al, 2008). The question whether astA-positive EAEC could be regarded as a health issue in Cameroon, in spite of its lack of association with diarrhoea is then posed.…”
Section: Discussionsupporting
confidence: 88%
“…AstA-positive EAEC were not significantly associated with diarrhoea in this study (26.1% in cases, 25.5% in controls). These results, in accordance with those reported from Nigeria (Okeke et al, 2000b), contrasted with those obtained during a similar investigation in Brazil (Zamboni et al, 2004) and in India (Anvikar et al, 2008). The question whether astA-positive EAEC could be regarded as a health issue in Cameroon, in spite of its lack of association with diarrhoea is then posed.…”
Section: Discussionsupporting
confidence: 88%
“…Findings showed that all subgroups had more imprecise ORs compared with the overall pooled OR and that only the statistically powerful studies (>80%) and those that used the "gold standard" HEp2 assay reflected the significant overall effect [ Figure 3a]. Second, using the Galbraith plot method, [17] five outliers were detected, showing three studies above [13,16,18] and two below [11,12] the confidence limits [ Figure 4]. The outcome of outlier analysis increased the number of significant ORs, narrowed all CIs, in the overall and subgroups conferring greater precision on the pooled ORs [ Figure 3b].…”
Section: Modifier Analysesmentioning
confidence: 93%
“…The dotted lines are positioned two units above and below the solid line and delimit an area in which, in the absence of statistical heterogeneity, the majority (95%) of the study results would be expected to lie. Those situated above [13,16,18] and below [11,12] …”
Section: Survey Of Meta-analyses Publications In Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Fosfolipídeos estão sendo identificados como potenciais receptores para BFP. Sabese ainda, que EPEC liga-se a fosfatidiletanolamina de maneira específica e dose dependente (BARNETT et al, 1999).…”
Section: Estágios Da Interação Entre Epec E Enterócitounclassified